Functional outcome of carcinoma tongue after primary surgical treatment - Sarkar, Palash Chandra; Hanif, M. Abu; Alam, K. M. Nurul; Rafiqul Islam, Mohammad; Akram, M. Shafiul; Rahman, S. M. Azizur; Badhan, Raisa Enayet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Majority of patients with oral malignancies appear in a late stage, with a low survival rate, despite advancements in imaging and therapy choices. Surgery is a well-known option among the various therapeutic techniques. In order to evaluate the functional outcome of carcinoma tongue among patients receiving primary surgery, the study was designed. Methods: This cross-sectional observational study was conducted at the department of otolaryngology, national institute of ENT and central hospital (Pvt.) limited, Dhaka. All histopathologically diagnosed case of carcinoma tongue undergone primary surgical treatment were approached for including into the study. Informed written consent was taken from each subject. Total 30 patients were included. After surgical intervention, functional outcome was measured by the performance status scale (PSS) for head and neck cancer. Data analysis was done by SPSS 20. Results: Total 30 patients of carcinoma tongue were included in this study. Base of tongue (66.6%) and oral tongue (33.3%) were present as advanced and early stage respectively. Hemiglossectomy (43.3%) was the most commonly used methods. Improvement was seen in 'eating in public' score and 'understandability of speech score at 4th month after surgery, which was not steady over subsequent follow-ups. Normalcy of diet score also showed improvement at 4 months follow-up but slowly declined afterwards. Overall, improvement in 'eating in public' understandability of speech' and normalcy of diet score were not statistically significant. Conclusions: Improvement of functional status was not statistically significant following primary surgical intervention in carcinoma tongue.